(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
The article focuses on the representation of striptease in Italy in the late 50s. While the unveiling of the female body became more and more pervasive - in posters, in magazines, in theaters, in cinematography - Italian moralists sought strategies to contain the phenomenon. At the same time, many courts issued acquittal sentences which, in fact, liberalized striptease. At the center of the dispute was not female nudity (which had been showed since at least a decade) but rather the rules of behavior of women, disputed between the will to control and the desire to look. In both cases, considered as an object of the male will.